Nurses' Perceptions of Factors Influencing Elder Self-neglect: A Qualitative Study - Meiliyang Wu; Chaohua Peng; Ye Chen; Mengmei Yuan; Meizhen Zhao; Chengshuang Wang; Tieying Zeng (Elsevier, 2020)
Purpose: Elder self-neglect is a global public health issue and should be taken seriously at large. Nurses, usually working directly with elderly patients, have a better understanding of what factors may cause elder self-neglect. In this qualitative study, we explored the influencing factors of elder self-neglect from the perception of nurses in the context of Chinese culture. Methods: Face-to-face, in-depth interviews were conducted from November 2018 to December 2018. Purposive sampling was used. Twenty one participants recruited from eight geriatric wards of a general hospital located in Wuhan were interviewed. A content analysis of qualitative nature was performed to analyze the data. Results: Our conceptual model illustrated the findings based on the three themes of the conflict between personal recognition and social judgment, the choice between current needs and individual beliefs, as well as the compromise between insufficient abilities and limited resources. Conclusion: Nurses together with family members and social workers can help older adults improve their awareness of self-neglect to bridge the gap with social judgment, learn to focus on their own needs, as well as seek as much support as possible. Nurses should also respect the autonomy and self-determination of elder self-neglecters because self-neglect is related to older adults' values. Furthermore, larger studies are needed to quantitatively test and refine the model.